2022
DOI: 10.1101/2022.10.26.22281446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genomic epidemiology of SARS-CoV-2 variants of concern in Kenya

Abstract: The emergence and establishment of SARS CoV 2 variants of concern presented a major global public health crisis across the world. There were six waves of SARS CoV 2 cases in Kenya that corresponded with the introduction and eventual dominance of the major SARS-COV-2 variants of concern, excepting the first 2 waves that were both wildtype virus. We estimate that more than 1000 SARS CoV 2 introductions occurred in the two-year epidemic period (March 2020 to September 2022) and a total of 930 introductions were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…However, we note that these sequences conform to molecular clock estimations of the emergence of Delta globally estimated around 19 October 2020 with an earliest possible date estimated as 06 September 2020 [55], Figure S5. A similar pattern of early emergence and slow rise to dominance is observed in several countries across the continent [34] and, in a more detailed study in Neighboring Kenya [56].…”
Section: Discussionsupporting
confidence: 75%
“…However, we note that these sequences conform to molecular clock estimations of the emergence of Delta globally estimated around 19 October 2020 with an earliest possible date estimated as 06 September 2020 [55], Figure S5. A similar pattern of early emergence and slow rise to dominance is observed in several countries across the continent [34] and, in a more detailed study in Neighboring Kenya [56].…”
Section: Discussionsupporting
confidence: 75%
“…In the present study, we document SARS-CoV-2 transmission patterns within households in coastal Kenya by analysing infections identified in a case-ascertained cohort (i.e. households enrolled if a member was confirmed case of SARS-CoV-2 or a contact of one) during successive local waves of infections 28 . We undertook detailed genomic analyses to identify patterns of SARS-CoV-2 introductions into households and to document the frequency and patterns of infection spread within households in coastal Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…In the samples analysed from Kenya this study, Alpha was the dominant variant between March 2021-May 2021 and was then replaced by Delta in May 2021, followed by Omicron in mid-December 2021, which is in keeping with epidemiological data from other regions of Kenya (24,25). Other studies have reported the Beta variant co-circulating with the Alpha variant in regions of Kenya (26). The HRM-VOC-2 assay used to screen all 506 samples in this study doesn’t detect the Beta VOC and no samples were identified as Beta in those that were sequenced, so it is unknown whether Beta was present in this sample set.…”
Section: Discussionmentioning
confidence: 88%
“…An HRM panel for detecting Delta, Omicron BA.1, BA. (26,28). This could be due to non-specific binding of the omicron primer sets to the RNA, or alternatively a mutation in one of the primer target sites resulting in a temperature shift of the peak that results in the shift of a peak into the Tm range for Omicron for HRM-VOC-2 resulting in the miscalling of the Omicron variant for these samples.…”
Section: Discussionmentioning
confidence: 99%